2018
DOI: 10.1002/jrs.5522
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra in LiH2PO4 and KLi(H2PO4)2: Mode assignment

Abstract: We report and analyze Raman spectra recorded on crystals of LiH 2 PO 4 (LDP) and KLi(H 2 PO 4 ) 2 (KLDP). We provide a new and complete assignment of Raman lines in both crystals from their behavior as function of temperature. Among internal vibrations, we discern the modes within PO 4 tetrahedra, the modes related to Li-O bonds, and those due to the O-H vibrations. In the wavenumber range between 300 and 600 cm −1 , the lines associated with O-P-O or Li-O show different temperature dependencies. The bands of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The peak at 1277 cm −1 was attributed to stretching of C-O stretching vibrations shifted to peak at 1256 cm −1 (-21) which attributed to stretching vibration of the PO 2− asymmetric vibrations (phosphate I) 79,84 . The signal at 1053 cm −1 was attributed to the PO 4 3− group vibration 85 and not shifted after the biosorption process. The presence of intense peaks in the region of 1000-1100 cm −1 is a characteristic of polysaccharides 80 .…”
Section: Desirability Function (Df)mentioning
confidence: 98%
“…The peak at 1277 cm −1 was attributed to stretching of C-O stretching vibrations shifted to peak at 1256 cm −1 (-21) which attributed to stretching vibration of the PO 2− asymmetric vibrations (phosphate I) 79,84 . The signal at 1053 cm −1 was attributed to the PO 4 3− group vibration 85 and not shifted after the biosorption process. The presence of intense peaks in the region of 1000-1100 cm −1 is a characteristic of polysaccharides 80 .…”
Section: Desirability Function (Df)mentioning
confidence: 98%
“…Ciszak et al [ 144 ] reported the Raman spectral analysis of ZrO 2 thermally grown on Zircaloy substrates irradiated with heavy ions and illucidated the effects of oxygen isotopic substitution. Dekhili et al [ 145 ] reported new and complete mode assignments of Raman spectra in LiH 2 PO 4 and KLi(H 2 PO 4 ) 2 . Flessa et al [ 146 ] described Raman mapping of 4‐MeV C and Si channeling implantation of 6H–SiC.…”
Section: Solid‐state Studiesmentioning
confidence: 99%